Implementation of Cipoo Model (Context, Input, Process, Output And Outcome) in Poverty Reduction Based on Prime Potentials (A Case Study of Wonogiri Regency) - Izza Mafruhah; Supriyono -; Nurul Istiqomah (Trunojoyo University of Madura, 2019)
Poverty is a classic problem caused by economic and non-economic factors such as cultural, sociological, political and geographical issues. Efforts to alleviate poverty can be done through community empowerment. Empowerment is the creation of an atmosphere or climate that allows excellent potential to grow. Wonogiri is the second largest regency in Central Java, with diverse prime potentials, but not yet able to boost its economic growth. This leads to relatively high poverty in this regency. GDP growth per capita is much lower than that of Solo Raya, Provincial and National, which shows that Wonogiri people's welfare is relatively lower compared to other regions.The main objective of this research is to develop a poverty reduction model based on prime potentials through the implementation of CIPOO (Context, Input, Process, Output and Outcome) model in Wonogiri by (1) identifying local resource-based economic potentials; (2) analyzing factors affecting community empowerment and participation in inclusive development activities; and (3) analyzing the development process of each subdistrict.The research method used is Sequential Mixed Method with analytical tools used include Geographic Information System (GIS), CIPOO analysis, Focus Group Discussion, in-depth interview, and Klassen Typology.The results showed that the greatest potential in Wonogiri district is agriculture especially horticulture, fisheries, plantation, animal husbandry, and tourism. The gap between sub-districts is very high as indicated by high Gini index and Klassen typology. Therefore, the poverty alleviation model with participatory CIPPO is appropriate for Wonogiri regency.